Increasing Student Learning Motivation with the Application of Ice Breaking in Grade IV of State Elementary School 262 Panyileukan Bandung City - Galuh Nur Insani; Haldini Reygita; Mutia Ade Syafitri; Deti Rostika (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The Ice breaking method itself is an activity applied by everyone to attract the focus of attention and melt the atmosphere in the room into its original state, which is an excited state (conducive again). The purpose of this study was to find out how much the influence of ice breaking in increasing learning motivation in students. This study used a quality method where researchers used observation methods on grade V students in one of the elementary schools in the Panyileukan area. Based on the results of the study, it can be concluded that ice breaking is very influential in increasing student learning motivation.